Microscopic aspects of lymphoid organs in the guinea pig (Cavia porcellus) - Fernanda Menezes de Oliveira e Silva; Marcio Nogueira Rodrigues; Érika Toledo da Fonseca; André Luis Rezende Franciolli; Maria Angelica Miglino (Biotemas)
Microscopy of lymphoid organs was studied in the guinea pig at different developmental stages – fetus, pup, and adult. Liver is a lobed organ, coated with a mesothelium, and it consists of sinusoids and cell plates in its parenchyma, named hepatocytes. Thymus is covered by a thin capsule of connective tissue which is protruded as septa into the entire organ. The parenchyma of each lobule is not clearly separated into a cortex and medulla. Hassall’s corpuscles are abundant. Lymph nodes are arranged into cortex and medulla. The cortex has germinal centers or lymphoid nodules, surrounded by diffuse lymphoid tissue. Spleen is divided into red and white pulp. Trabeculae of connective tissue are protruded into the spleen from the capsule; however, they are sparsely found around the red and white pulps. Germinal centers were found in the white pulp, where small and large lymphocytes and lymphoblasts can be found. Since the guinea pig is regarded as an important model for morphological studies due to its closeness to human beings, this article raises relevant information on the structural components of the lymphoid system in these animals, providing a new source of data to other knowledge fields.